Oroxylin A ameliorates AKI-to-CKD transition through maintaining PPARα-BNIP3 signaling-mediated mitochondrial homeostasis - Yao, Mengying; Qin, Shaozong; Xiong, Jiachuan; Xin, Wang; Guan, Xu; Gong, Shuiqin; Chen, Jing; Liu, Yong; Zhang, Bo; Zhao, Jinghong; Huang, Yinghui (Frontiers in Pharmacology, 2022)
Background: Acute kidney injury (AKI) occurs in approximately 7–18% of all hospitalizations, but there are currently no effective drug therapy for preventing AKI or delaying its progression to chronic kidney disease (CKD). Recent studies have shown that Scutellaria baicalensis, a traditional Chinese herb, could attenuate cisplatin-induced AKI, although the mechanism remains elusive. Further, it is unknown whether its major active component, Oroxylin A (OA), can alleviate kidney injury. Methods: The therapeutic effect of OA was evaluated by using ischemia-reperfusion (IR) and cisplatin mediated-AKI mice and HK-2 cells under hypoxia-reoxygenation (HR) conditions. HE staining, transmission electron microscopy, flow cytometry, immunofluorescence, qPCR, Western blot, PPARα inhibitor, BNIP3 siRNA and ChIP assay were used to explore the role and mechanism of OA in AKI. Results: OA ameliorated tubular damage and dramatically decreased serum creatinine (Scr) and urea nitrogen (BUN), and the expressions of renal injury markers (Kim-1, Ngal) in AKI mice induced by both IR injury and cisplatin, as well as attenuating AKI-to-CKD transition. In vitro experiments showed that OA alleviated HR-induced mitochondrial homeostasis imbalance in renal tubular epithelial cells. Mechanistically, OA dose-dependently induced the expression of Bcl-2/adenovirus E1B 19-kDa interacting protein (BNIP3), while knockdown of BNIP3 expression reversed the protection of OA against HR-mediated mitochondrial injury. Network pharmacological analysis and experimental validation suggested that OA enhanced BNIP3 expression via upregulating the expression of peroxisome proliferator activated receptor alpha (PPARα), which induced the transcription of BNIP3 via directly binding to its promoter region. Both in vitro and in vivo experiments confirmed that the renoprotective effect of OA was dramatically reduced by GW6471, a PPARα antagonist. Conclusion: Our findings revealed that OA ameliorates AKI-to-CKD transition by maintaining mitochondrial homeostasis through inducing PPARα-BNIP3 signaling pathway, indicating that OA may serve as a candidate therapeutic strategy for alleviating AKI and CKD.